PENINGKATAN KOMPETENSI PROFESIONAL GURU PAK MELALUI LITERASI DIGITAL - Jutela; Yonatan Alex Arifianto (Institut Agama Kristen Negeri Kupang, 2022)
increasing professional competence is where someone who has expertise in their field and masters their field and how to improve to be better in the field taken by someone, increase professional competence how to improve in the field that has been taken and must be an expert in the field that is very important and must be done. And the research method taken and which will be explained is through a qualitative method with the philosophy of positivism, where the research mindset uses a deductive quantitative method. So the teacher must have competence and the teacher also has the ability and has many ideas in improving student learning during this covid 19 pandemic, where the teacher must have a way to attract the attention of students to study better and instill good character for students.